A combination of rules govern fruit trait preference by frugivorous bat and bird species: nutrients, defence and size - Rojas, Tobias Nicolas; Bruzzone, Octavio Augusto; Zampini, Iris Catiana; Isla, Maria Ines; Blendinger, Pedro Gerardo (Elsevier, 2021)
Several hypotheses explain how sensory, anatomical and physiological constraints drive fruit preference in frugivores. Optimal diet theory (ODT) states that frugivores make decisions based on the energy contained in food. In contrast, geometry of nutrition (GN) states that animals balance their macronutrient intake instead, opting for rough energy. The defence trade-off hypothesis (DTH) assumes a negative relationship between secondary compounds and fruit preference. Finally, the size-matching hypothesis (SMH) states that frugivores are more attracted to fruits that are easier to handle and consume. We tested these four hypotheses by offering paired fruit species to three fruit-eating animal species in captivity that either chew fruit in the beak or mouth (‘masher’: 1 bird species, 1 bat species) or swallow whole fruits (‘gulper’: 1 bird species), from which we built a ranking of fruit preference.We then explored the importance of 13 fruit traits in explaining fruit preference. The masher bird was the only species whose fruit preference pattern corresponded with GN. Fruit preference of the masher and gulper bird species supported DTH and SMH, while fruit preference by the bat species was not related to any analysed trait. More than one single rule governs fruit preference in different frugivore species. Fruit preferences of functionally different frugivore species are affected by particular fruit traits, which they either select or avoid. The search for specific macronutrients, while avoiding toxicity in fruits matching the anatomical limitations of frugivores, could lead to complementary foraging choices. Variability between seed disperser species in their search for easily manageable fruits allows achieving a complementary fruit diet, with preferred and avoided traits. It can be an important driver of fruit trait diversity in fleshy-fruited plant assemblages.